Activated Carbons Prepared from Oil Palm Shells: Characterisations and Application for Column Separation of Heavy Metals - Anthony Joseph, Collin Glen Joseph (2002)
Wastes from agricultural products are abundant, suitable to be used as precursor for producing activated carbons. These wastes, instead of causing significant disposal problems, can be turned into by-products for industries by utilizing them fur manufacturing activated carbons. Carbonization and activation processes were done in the Tubular Carbolite Furnace. N₂ gas was flowed for the first 3 hours followed by CO₂ gas for the next 1 hour on the precursor at the constant temperature of 500°C. Par the H₃PO₄ impregnation, 30 grams of the palm shells were impregnated with 15 ml ofH3P04 and diluted with 100 ml of distilled water to produce 2.2 M H₃PO₄ solution. For the K₃PO₄, 30 grams of palm shells were impregnated with 9 g of K₃PO₄ and diluted with 100 ml of distilled water to produce 9% w/w K₃PO₄ solution. For the KOH impregnation, 30 grams or palm shells were impregnated with 9 g of KOH and diluted with 100 ml of distilled water to produce 9 % w/w KOH solution.